Peran Kepemimpinan Transformasional dan Motivasi Kerja terhadap Komitmen Organisasional Pegawai di Masa Pandemi Covid-19 di Moderasi Work From Home/Work From Office di RSUD Jati Padang Jakarta Selatan - Anita Theresia Junianty; Rina Anindita; Muh. Natsir Nugroho (Jurnal Health Sains, 2021)
The current pandemic in Indonesia has allowed the government to quickly overcome the improvement of public health due to the Corona Virus (Covid-19) by issuing SE Nomor 58 Tahun 2020 concerning the Work Procedure for State Civil Servants of the New Normal Order to establish a work entry system and provisions on working hours used remote working system. Remote work system established by the government through flexibility in work location arrangements, namely working from home(WFH) / office from the office (WFO). This situation can cause a decrease in enthusiasm and concentration at work. As a result of the increase in work cases with the new work system, it has led to a crisis of boredom or boredom for employees in providing services in hospitals. This study aims to analyze the effect of transformational leadership and work motivation on organizational commitment as moderated by working from home / working from the office at RSUD Jati Padang. The design of this research is a quantitative survey with a causal approach. The data source is a primary data survey method with a questionnaire instrument via google form which is distributed to 90 samples. The results of the questionnaire were analyzed using Moderated Regression Analysis and described using descriptive statistics. The results showed that transformational leadership has a positive effect on organizational commitment. However, the findings in this study were that transformational leadership and work motivation moderated by working from home / office weakened the organizational commitment of employees at RSUD Jati Padang. For further research at Jati Padang Hospital, it is more focused on other moderating variables